2011
DOI: 10.1002/clen.201000422
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Characteristics of Pollutants and Their Mutual Influence in Highway Runoff

Abstract: Many environmental pollution issues from highway runoff increasingly become a serious concern, which has been revealed by many previous studies. However, very less information is available on the distribution characteristics of pollutants and their mutual influence in highway runoff. In this paper, the partitioning of pollutant and particle size distribution were investigated based on the initial road runoff of 47 rainfall events from July 2007 to May 2009 on the Lukou section of the Nanjing Airport Expressway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…It is known that antecedent dry period, storm intensity and traffic density are relevant factors influencing the runoff quality Brodie and Dunn, 2010;Zuo et al, 2011). No significant differences were found between water quality variables in X12 and X22 (p>0.05), so all the values obtained from both roads were used in a multivariate analysis which showed that antecedent dry period was the most significant variable for TP and TN whereas rainfall intensity was the most influential for COD and TSS.…”
Section: Water Quality Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that antecedent dry period, storm intensity and traffic density are relevant factors influencing the runoff quality Brodie and Dunn, 2010;Zuo et al, 2011). No significant differences were found between water quality variables in X12 and X22 (p>0.05), so all the values obtained from both roads were used in a multivariate analysis which showed that antecedent dry period was the most significant variable for TP and TN whereas rainfall intensity was the most influential for COD and TSS.…”
Section: Water Quality Resultsmentioning
confidence: 99%
“…Low correlation coefficients have been found between rainfall, rainfall intensity, temperature, and antecedent dry period with particulate pollutants, whereas the coefficient between rainfall duration and particulate pollutants was positive and relatively large [19].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…This means that TN build-up on roof surfaces could be relatively more variable for the <1 mm particle size while TS, TOC, and TP build-up are relatively more variable in the 1-150 mm size range in the case of roof surfaces. This can be attributed to the fact that nitrogen is primarily transported by stormwater in dissolved form while other pollutants such as organic matter and phosphorus could be more commonly present in particulate form [21][22][23].…”
Section: Variability Of Pollutant Build-up Loads On Roof and Road Surmentioning
confidence: 99%
“…Vijayaraghavan et al[3] claimed the adsorption abilities of 24.2mg Zn per g Sargassum biomass. This implied that the CM could be made use of the removal of heavy metals in water samples from various sources.3.5 Application of the used adsorbent to road runoffRainfall and rainfall intensity were two important factors determining the amount of pollutants in road runoff[15], and these factors wre related to rainfall events. Meanwhile, rainfall events have randomness and uncertainties.…”
mentioning
confidence: 99%